Effects of Pt and La doping on the superconductivity of CaFe2As2: Kondo effects - BOYRAZ, CİHAT (ELSEVIER SCI LTD, 2021)
We report the magnetic properties of CaFe(2)A(s)2, CaFe1.9Pt0.1As2, and Ca0.9La0.1Fe1.9Pt0.1As2 compounds in a wide temperature range of 5-300 K in the field up to 9 T. We have observed a well-defined anomaly in the resistivity around 165 K, which manifests clearly a well-known first order magneto structural phase transition from paramagnetic-tetragonal (T) state to antiferromagnetic orthorhombic (Ort) one. Pt doped and Pt and La co-doped CaFe2As2 samples exhibit a Kondo lattice behavior. The critical current density, J(c), and normalized pinning force F-p/F-p,F-max as a function of the applied field are obtained. Moreover, the normalized pinning force density, F-p/F-p,F- max curves versus h = H/H-irr were scaled using the Dew-Hughes model. Hence, the natures of the flux-pinning centers for these samples are revealed. Based on the results obtained from these analyses, we claim that the superconductivity in as-prepared CaFe2As2 occurs on the grain-boundary with the filamentary character.
Keywords: Bulk superconductivity; The electronic band structure; Kondo effect; Pt and La-Doped CaFe2As2; The filamentary character; And magnetic properties; HIGH-TEMPERATURE SUPERCONDUCTIVITY; IRON; DEPENDENCE; MAGNETIZATION; HYSTERESIS; TRANSPORT; PNICTIDES; PRESSURE; VORTICES; CURRENTS